Information and Communication Technology in the Teaching of History - Deletić, Zdravko M. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Based on the teaching experience, the study of literature and theoretical knowledge, the paper discusses the possibilities of using computers and digital media by foreign teachers and students in the preparation for teaching history, about the ability of students to learn using information technology at school, in extracurricular activities, and homework. Highlights of the use of electronic media in the teaching of history are the high availability of documents (texts, photographs, maps) and the abundance of information of scientific, journalistic, and informative character. In addition to the ability to search the databases and sites available on the Internet, computer technology enables fast and high-quality word processing, creation of new documents and presentations, creation of diverse databases, real-time information exchange of documents, personal communications, printing of text, etc. Working with electronic devices and digitized documents enables students to study with the application of multiple sources of knowledge, exploiting personal interests and abilities, and provides numerous opportunities for active and creative learning. Besides the numerous advantages, it is important to mention some restrictions on the use of electronic media in the teaching of history, in the first place, the availability of documents and the interpretation of the history by questionable scholars (truthfulness), as well as the fact that the teacher does not have an insight in how students use the document available on the Internet.